Does New Health Information Affect Health Behavior? The Effect of Health Events on Smoking Cessation - Christian Bünnings (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
This paper investigates whether new health information affects smoking behavior. Interpreting three distinct categories of health events as different information, the paper also tests whether behavioral change depends on the type of information received. Based on retrospectively reported data on smoking behavior from the Swiss Household Panel, a linear probability model is applied to estimate the effects of three different health events on the decision to quit smoking. The empirical results yield robust evidence that smokers respond differently to health events that are due to different causes. Suffering from physical health problems increases the inclination to stop smoking, the opposite holds true for mental disorders, while accidents do not affect health behavior at all. Analyses of effect heterogeneity further reveal that the same type of information affects various subgroups of the population differently. – – Dieses Papier untersucht die Fragestellung, ob neue Gesundheitsinformationen das individuelle Rauchverhalten beeinflussen. Um darüber hinaus zu testen, ob die Verhaltensänderung von der Art der Information abhängt, werden drei verschiedene Gesundheitsereignisse als unterschiedliche Information interpretiert. Mittels retrospektiver Informationen zum Rauchverhalten, basierend auf dem Schweizer Haushalt-Panel (SHP), werden die Effekte dreier Gesundheitsereignisse auf die Entscheidung das Rauchen aufzugeben durch ein lineares Wahrscheinlichkeitsmodell geschätzt. Die empirischen Ergebnisse liefern robuste Evidenz, dass Raucher unterschiedlich auf verschiedene Gesundheitsereignisse reagieren. Während physische Gesundheitsprobleme die Wahrscheinlichkeit das Rauchen aufzugeben erhöhen, trifft das Gegenteil auf mentale Gesundheitsprobleme zu, während Unfälle das Gesundheitsverhalten nicht beeinflussen. Heterogenitätsanalysen zeigen zudem, dass die gleiche Art von Information verschiedene Teilgruppen unterschiedlich beeinflusst.
Keywords: C23; I10; 330; health events; behavioral change; smoking cessation; retrospective data